Luminescence dating of sand wedges constrains the Late Wisconsin (MIS 2) permafrost interval in the upper Midwest, USA. (17th August 2021) - Schaetzl, Randall J.; Running, Garry; Larson, Phillip; Rittenour, Tammy; Yansa, Catherine; Faulkner, Douglas
Abstract : Large parts of the upper Midwest, USA were impacted by permafrost during the Last Glacial Maximum (LGM). Even though permafrost persisted as the Laurentide Ice Sheet began to recede, direct age control of this interval is largely lacking. To better temporally constrain the permafrost interval in western Wisconsin, we identified two sites, outside the Late Wisconsin (MIS 2) glacial limit, that contain relict, ice‐wedge pseudomorphs, initially interpreted to be sand wedges, hosted within well‐drained outwash deposits. The pre‐Wisconsin (>MIS 5) host material commonly displays up‐turned bedding near the contact with the wedges, indicative of well‐formed features. The wedges are filled with well‐sorted, gravel‐free, medium and fine sands, and lack evidence of post‐formational disturbance, pointing to an aeolian sand infill and confirming them as sand wedges. Ventifacts on nearby uplands attest to windy conditions here in the past. Optically stimulated luminescence (OSL) ages on five sand wedges indicate that they filled with sand between c . 19.3 and 18.3 ka at the southerly site and between c . 15.1 and 14.7 ka at the northerly site, which is closer to the LGM margin. Sand wedges at the latter site were wider and had more complex morphologies, possibly suggesting a longer interval of formation and/or more intense permafrost. We also examined a site along a ridge crest, between the two wedge sites, which displayed interbedded loess and sand, dated by OSL to 12.7 ka. Together, these results point to dry, cold, windy conditions in west‐central Wisconsin, within 100 km of the LGM limit. At this time, aeolian sands were being transported across a landscape with (at least scattered) permafrost. The OSL results suggest multiple phases, or perhaps time‐transgressive, sand‐wedge formation, associated with permafrost between c . 19 and 15 ka, with dry, windy (and likely, cold) conditions persisting until at least 12.7 ka.